Effects of temperature on embryonic development of banana weevil, Cosmopolites sordidus - Traoré, L.; Gold, C.; Pilon, J.; Boivin, G. (African Journals Online, 1993)
Developemental threshold and thermal requirements for eggs of banana weevil, Cosmopolites sordidus Germar, were determined under laboratory conditions at constant temperatures of 15,18,25,27,30,32 and 34 °C and a photoperiod of 12:12 L/D. The duration of the egg stage decreased from 34.9 days at 15° C to 4.9 days at 30° C, then increased again to 5.3 days at 32° C. Eggs did not hatch above the latter temperature although signs of embryonic development, such as formation of the head capsule, could be observed. Simple linear regression revealed a developmental threshold of 12° C and a thermal requirement of 89 days-degrees average. Highest rates of eclosion occurred between 25° C and 30° C.